The Potential of Renewable Energy in Reducing Carbon Footprint in Developing Countries - Hidayat, Rahmat; Chai, Nong; Pao, Chai (Journal of Humanities Research Sustainability, 2024)
Background. Increasing carbon emissions in developing countries is a serious challenge in climate change mitigation efforts. Renewable energies such as solar, wind, and biomass have great potential to reduce carbon footprint while increasing access to sustainable energy. Purpose. This study aims to analyze the potential of renewable energy in reducing carbon emissions in developing countries, as well as identify the main obstacles that hinder its utilization. Method. The research method uses a quantitative and qualitative approach, involving data analysis from various international reports as well as case studies from several developing countries. The data was analyzed to measure the potential of renewable energy, the level of utilization, and its impact on reducing carbon emissions. Results. The results show that although the potential of renewable energy is high, its utilization is still low due to infrastructure limitations, inconsistent policies, and inadequate funding. Conclusion. The study concludes that renewable energy can be an important solution in reducing carbon footprints in developing countries with stable policy support and international collaboration. Investment in infrastructure and local capacity building is needed to overcome implementation constraints.